Theories and models used in analyzing fishermen behavior: insights on fisheries management processes - Naranjo-Madrigal, Helven (2017)
As part of the decision-making process in fisheries management, attention to aspects with regard to regarding the human dimension of fishing has increased, in addition to the ecological dimension. Within the human dimension, the fishing fleet dynamics component has been analyzed using models and theories that emphasize fleet behavior and pay less attention to fishermen’s behavior as an individual or groups of individuals. This literature review is focused on studies that have analyzed aspects of fishermen behavior using theories and models that explain and predict their behavior. It was found that economic drivers per se do not explain the complexity of the fisherman’s decision-making process; on the contrary, a number of non-monetary aspects are implicit in the choices made by fishermen in the short and long term. Models that include information from different disciplines and trans-disciplinary approaches better explain fishermen’s decisions in relation to effort, economic incentives, catches, regulations, and aspects related to their culture, lifestyle, livelihood strategies, job satisfaction and perception of wellbeing. Based on this literature review, a conceptual framework is proposed for socio-ecological management in order to integrate the drivers related to fishermen behavior and their relationship with the ecosystems on which they depend.